Exploring the potential of aloe vera and coconut oil n natural toothpaste tablets - Zulkifli, Muhammad Nazrul Afiq; Mustakim, Muhammad Irfan; Muhamad Zaki, Nurul Ain Jaaizah; Mohd Bakti, Nur Syabila Husna; Zakaria, Nurul Aimi; Mohamed Zabidi, Zubainun; Alias, Ahmad Nazib (Universiti Teknologi MARA, Kedah, 2023)
Plastic toothpaste tubes take an extremely long time to biodegrade. The initiative to produce natural toothpaste tablets can be a big step toward lessening the plastics nightmare the Earth currently finds itself. However, it is very necessary to make sure toothpaste tablet production process and raw materials used does not intent any harm to environment. Furthermore, natural toothpaste tablets use plant-based ingredients such as aloe vera and coconut oil which are a better version compared to chemical toothpaste. To test the hypothesis that durability and efficacy will influence the quality of toothpaste production, water resistance method was used to examine the durability of the toothpaste tablets. In addition, eggshell experiment method was also used to study the effectiveness of natural toothpaste tablets. The result showed that toothpaste tablets that been produced during this project wasproved effective by using all natural ingredients. Sample 3 is the best and most suitable to produce an effective toothpaste tablet as it gives ideal ingredients measurement and perfect texture as pills. These result suggest that natural tablets toothpaste is a better version compared to chemical toothpaste because of it using all natural ingredients. This can be proved that the natural ingredient that beenused which is coconut oil can help in the reduction of plaque formation on the teeth. Besides, tablets toothpaste is not using plastic toothpaste tubes as its storage place. Hence, by this initiative, which is using natural tablets toothpaste, it will help to reduce the environmental pollution. This research mainly deals with making non-chemical based, eco-friendly and cost-effective tablet toothpaste from aloe vera and coconut oil also replace the normally used toothpaste in future.